2014
DOI: 10.1093/mutage/geu086
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells as a novel platform for simultaneous evaluation of cytotoxicity and genotoxicity of pharmaceuticals

Abstract: The in vitro micronucleus test is a well-known test for the screening of genotoxic compounds. However until now, most studies have been performed on either human peripheral lymphocytes or established cancer cell lines. This study provides human mesenchymal stem cells as an alternative to the conventional micronucleus test. We grew umbilical cord mesenchymal stem cells (UC-MSCs) on coverslips eliminating the cumbersome technique involving hypotonic treatment, fixation and preparing smears required for suspensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 53 publications
3
20
3
Order By: Relevance
“…Cells are constantly exposed to reactive oxygen species including those metabolically generated as products of aerobic respiration [ 32 , 33 ] and those originated from environmental pollutants [ 34 ]. It has been observed that hydrogen peroxide concentrations above 100 μ M are cytotoxic and genotoxic in A549 cells [ 35 ] causing DNA damage [ 36 ] and inducing the catalytic activities of DNA topoisomerase complexes [ 37 39 ]. Furthermore, the H 2 O 2 -induced damage could be also revealed by the oxidation of DNA bases, for instance, guanine adducts like 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxo-dG) [ 40 ].…”
Section: H 2 O 2 Indmentioning
confidence: 99%
“…Cells are constantly exposed to reactive oxygen species including those metabolically generated as products of aerobic respiration [ 32 , 33 ] and those originated from environmental pollutants [ 34 ]. It has been observed that hydrogen peroxide concentrations above 100 μ M are cytotoxic and genotoxic in A549 cells [ 35 ] causing DNA damage [ 36 ] and inducing the catalytic activities of DNA topoisomerase complexes [ 37 39 ]. Furthermore, the H 2 O 2 -induced damage could be also revealed by the oxidation of DNA bases, for instance, guanine adducts like 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxo-dG) [ 40 ].…”
Section: H 2 O 2 Indmentioning
confidence: 99%
“…Studies of DNA damage at the chromosome level are needed in toxicogenetic studies (Sharma et. al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study by Latifpour et al [52] report that human umbilical cord (hUCMSCs) can trans-differentiate into primordial like GCs (PGCs) when in vitro culture was performed under specific condition (bone morphogenetic protein 4 followed by retinoic acid). Hence, MSCs can be efficiently utilized to study mechanisms and pathways of different toxicants provoking etiology of many diseases, toxicity testing, evaluation of cytotoxicity and genotoxicity of pharmaceuticals and toxicity screening of chemicals that induce neurotoxicity, cardiotoxicity, hepatotoxicity, reprotoxicity, and drug discovery [53]. For example, development of anti-obesity drugs requires adipocytes that can be used to test whether any chemicals and toxicants can affect this process.…”
Section: Tripathy and Mohantymentioning
confidence: 99%
“…So, MSCs were shown to be capable of inducing angiogenesis and restoring the number of ovarian follicles and corpora lutea in ovaries [71]. hUCMSCs can differentiate into PGC under specific in vitro condition [53]. …”
Section: Mscs and Reproductive Toxicitymentioning
confidence: 99%